First record of Thalassiosira catharinensis (Bacillariophyta) from argentinean marine coastal waters. - Andrea S. Lavigne; Inés Sunesen; Eugenia A. Sar (Boletín de la Sociedad Argentina de Botánica, 2018)
Several ultrastructural analyses of taxa belonging to the genus Thalassiosira from Argentinean coastal waters were carried out, nevertheless, the smaller fraction of the nanoplanktonic Thalassiosira was frequently overlooked. The aim of this study is to show the morphological variation of T. catharinensis, to compare material found in marine coastal waters of Anegada Bay, Province of Buenos Aires, with the material analyzed in the protologue and allied taxa, and to record the species for the first time in Argentina, extending its distribution.